Penerapan Metode AHP dan SAW Pada Sistem Pendukung Keputusan Untuk Menentukan Pengalokasian Dana BOS - Gina Sania; Ilka Zufria; M. Fakhriza (Institut Shanti Bhuana, 2024)
SMP N 7 Padang Sidempuan encountered challenges in optimally allocating the School Operational Assistance Fund (BOS). The school's administration faced difficulties in determining the prioritization of fund usage during each period. The suboptimal utilization of the BOS could impede the achievement of national educational objectives and have adverse effects on human resource capabilities. This study combined theAHP and SAW algorithms to determine the priority allocation of the School Operational Assistance Fund (BOS). The objective was to develop a web-based Decision Support System for budget management at SMP Negeri 7 Padang Sidempuan. With this approach, a system capable of determining the priority sequencefor BOS allocation based on its components was established. The research resulted in an integrated decision support system in the form of a website. This system effectively determined the priority sequence for BOS allocation based on various relevant components. With the implementation of this system, SMP N 7 Padang Sidempuan successfully managed the BOS, thereby maximizing its impact on improving the quality of education.